2022
DOI: 10.1037/pspi0000383
|View full text |Cite
|
Sign up to set email alerts
|

What counts as discrimination? How principles of merit shape fairness of demographic decisions.

Abstract: Demographic attributes (e.g., age, disability, race) frequently affect people's decisions. We provide a novel perspective as to why such discrimination persists: Meritocratic principles lead people to perceive some demographic attributes as fair to use, rather than as discriminatory. Specifically, we theorize that meritocracy requires that controllable and relevant inputs determine outcomes; as a result, perceived controllability and relevance affect the degree to which demographic attributes are perceived as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…In present American contexts, meritocracy shapes the foundations of self-regard. Meritocracy requires that resources are allocated based on internal, relevant factors, and specifically not factors like group membership, parental status, or personal connections (Belmi, Phillips, Laurin, & Engstrom, 2020; Son Hing et al, 2011; Tomova Shakur & Phillips, 2020). Many Americans believe meritocracy both should be and is the rule by which social goods are distributed (Son Hing et al, 2011).…”
Section: Self-regard Shaped By Meritocracymentioning
confidence: 99%
“…In present American contexts, meritocracy shapes the foundations of self-regard. Meritocracy requires that resources are allocated based on internal, relevant factors, and specifically not factors like group membership, parental status, or personal connections (Belmi, Phillips, Laurin, & Engstrom, 2020; Son Hing et al, 2011; Tomova Shakur & Phillips, 2020). Many Americans believe meritocracy both should be and is the rule by which social goods are distributed (Son Hing et al, 2011).…”
Section: Self-regard Shaped By Meritocracymentioning
confidence: 99%
“…These stereotypes can even legitimize paternalistic attitudes that limit women’s options and freedoms (including whether they should be hired for certain positions), because limiting options and freedoms are judged to be in their “best interest” (Glick & Fiske, 2001a, 2001b; Hideg & Ferris, 2016). Some demographic attributes are even judged as fair to incorporate into hiring decisions, because they are perceived to be relevant to some positions and occupations (Tomova Shakur & Phillips, 2022). So, certain groups may be discriminated against in hiring decisions, not despite beliefs that discrimination is unfair, but because people actually believe it is fair.…”
Section: Discussionmentioning
confidence: 99%
“…relevant to some positions and occupations (Tomova Shakur & Phillips, 2022). So, certain groups may be discriminated against in hiring decisions, not despite beliefs that discrimination is unfair, but because people actually believe it is fair.…”
Section: Discussionmentioning
confidence: 99%
“…Legal scholars (such as Hoffman, 2021: 1519, emphasis added) also argue that "common sense dictates that it is unjust for workers to suffer adverse consequences solely because of traits they were born with or cannot modify." Laypeople too think controllability and relevance justify hiring practices (Shakur & Phillips, 2022). 3 In some cases, perhaps introversion is not considered bad in itself.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we will focus on what, surely, most readers will regard as a claim in greater need of support, i.e., that personality discrimination is in many ways akin to race and sex discrimination morally speaking. 6 A recent study (Shakur & Phillips, 2022) examined how people think about demographic attributes used in hiring. The study found that people rely on controllability and relevance dimensions to justify their perceptions of hiring practices; largely associating uncontrollable, irrelevant attributes, such as race and sex, with discrimination.…”
Section: Introductionmentioning
confidence: 99%